2017
DOI: 10.1136/bmj.j4030
|View full text |Cite
|
Sign up to set email alerts
|

Beating type 2 diabetes into remission

Abstract: Remission of diabetes (no longer having diabetes, at least for a period) is clearly attainable for some, possibly many, patients but is currently very rarely achieved or recorded. Greater awareness, documentation, and surveillance of remissions should improve health outcomes and reduce healthcare costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 9 publications
0
61
0
Order By: Relevance
“…If weight gain causes type 2 diabetes in susceptible individuals, would weight loss reverse the disease? A recent analysis in the BMJ [2] would suggest that it can.…”
Section: From the Editormentioning
confidence: 99%
See 3 more Smart Citations
“…If weight gain causes type 2 diabetes in susceptible individuals, would weight loss reverse the disease? A recent analysis in the BMJ [2] would suggest that it can.…”
Section: From the Editormentioning
confidence: 99%
“…Louise McCombie and her colleagues [2] from the University of Glasgow, Scotland, point out that type 2 diabetes is generally regarded as progressive and incurable. In the UK alone this disease now affects 5 -10% of the population.…”
Section: From the Editormentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research has shown that type 2 diabetes need not be a permanent condition, and that remission from the disease is possible following substantial weight loss . In recognition of this, the clinical coding system routinely used across UK health care has a specific code for those who successfully achieve and meet the criteria for diabetes remission . While long‐term outcomes have yet to be established, there seems little doubt that having an HbA 1c in the non‐diabetic range is likely to herald reduced long‐term vascular risk and justify lower travel insurance premiums …”
Section: Introductionmentioning
confidence: 99%